2020
DOI: 10.1080/08856257.2020.1748430
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Slovenian parents towards pre-school inclusion

Abstract: The attitudes of parents involved in the process of inclusion are of paramount importance. The aim of this study was to examine parents' attitudes towards the constructs associated with preschool inclusion with two goals, which were related to construct dimensions and differences in parents' attitudes regarding whether or not they have a child with SEN. Among 296 parents, selected by the cluster sampling technique, 202 parents with children in classrooms in Slovenian Carinthia (85 had a child with SEN) partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
(47 reference statements)
0
8
0
1
Order By: Relevance
“…Researchers Schmidt, Krivec, and Basti (2020) used a method called "cluster sampling" to talk to 296 parents in Slovakia, 85 of whom had children with special educational needs (SEN), to find out what they thought about the ideas behind preschool inclusion. In this study, it was found that parents of children with SEN were more open to inclusion, had a more positive view of the social effects and benefits of inclusion for both children with and without SEN, and were less worried about how inclusion would affect children without SEN (Schmidt et al, 2020). The IE analysis that comes next will pay more attention to the details of how to teach.…”
Section: Community/parents'' Attitudes Towards Inclusionmentioning
confidence: 74%
“…Researchers Schmidt, Krivec, and Basti (2020) used a method called "cluster sampling" to talk to 296 parents in Slovakia, 85 of whom had children with special educational needs (SEN), to find out what they thought about the ideas behind preschool inclusion. In this study, it was found that parents of children with SEN were more open to inclusion, had a more positive view of the social effects and benefits of inclusion for both children with and without SEN, and were less worried about how inclusion would affect children without SEN (Schmidt et al, 2020). The IE analysis that comes next will pay more attention to the details of how to teach.…”
Section: Community/parents'' Attitudes Towards Inclusionmentioning
confidence: 74%
“…Parents have also reported that exposure to diversity in inclusive education helps their young ones demonstrate more open-mindedness and acceptance towards individual differences(Peetsma, 2009).Schmidt, Krivec and Bastič(2020) conducted the study in Slovakia with the aim to examine parents" attitudes towards the constructs associated with pre-school inclusion using the cluster sampling method n= 296 of which n=85 had children with SEN. The results showed that parents of children with SEN are more open to inclusion, perceived positive social effects and benefits for children with and without SEN and had fewer negative feelings about the inclusion effects on children without SEN, than parents of children without SEN (Schmidt et al, 2020). The subsequent analysis in the next category will dwell more on the pedagogical complexities in IE.…”
Section: Community/parents" Attitudes Towards Inclusionmentioning
confidence: 93%
“…International policies and treaties offer guidelines for including students with special educational needs and disabilities in regular schools (United Nations International Children's Emergency Fund [UNICEF], 2017). Although this requirement aims to promote better academic, social, personal and emotional results for students with special educational needs and disabilities (Schmidt et al 2020), it also presents challenges, for example, when developing educational curricula or teaching strategies for regular classrooms. Moreover, special education teachers' role in academic settings and initial teacher training need considering.…”
Section: A Global Void: Special Education Teachers' Initial Training ...mentioning
confidence: 99%